2018
DOI: 10.1038/s41598-018-25786-x
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal water-in-oil nanocarriers of nitric oxide for triggering penile erection

Abstract: Men’s sexual health can have significant effects on a man’s self-esteem, sexual relationship and male reproductive functions. Although commercially available drugs (e.g., VIAGRA and CIALIS) show effective treatment of erectile dysfunction (ED), patients with severe ED fail to respond to these medicines. Topical nitric-oxide (NO) delivery to penis can be a painless, alternative solution with severe ED because NO triggers erection and diffuses to the trabecular arteries and smooth muscles in the penis. We here d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Blocking nitric oxide synthesis increases local arterial stiffness. NO is one of the most crucial mediators in erection physiology (Kinlay et al, 2001;Nam, Yoo, Kim, Kim, & Heo, 2018;Wilkinson et al, 2002). The fact that NO is involved in aetiology of both ED and arteriosclerosis is suggestive of an association between these two conditions.…”
Section: Discussion and Con Clus I Onmentioning
confidence: 99%
“…Blocking nitric oxide synthesis increases local arterial stiffness. NO is one of the most crucial mediators in erection physiology (Kinlay et al, 2001;Nam, Yoo, Kim, Kim, & Heo, 2018;Wilkinson et al, 2002). The fact that NO is involved in aetiology of both ED and arteriosclerosis is suggestive of an association between these two conditions.…”
Section: Discussion and Con Clus I Onmentioning
confidence: 99%
“…The study concluded that NO-NEs could be used as a topical drug delivery system for the treatment of ED patients and those who have poor drug reactions to phosphodiesterase 5 inhibitors. 50 This study is promising, but there is limited evidence on its use for the treatment of ED in humans. However, more clinical research is needed to evaluate the therapeutic efficacy and safety before is recommended for humans.…”
Section: Nanomedicine For Men Erectile Dysfunctionmentioning
confidence: 95%
“…Shortly, we should conduct clinical research that evaluates the efficacy and safety of this novel NO nanoparticle gel for the mitigation of male ED. In another study by Nam et al 50 prepared NO loaded waterin-oil (w/o) nanoemulsions (NEs) and examined the safety and efficacy of topical application of NO-NEs on the penile skin of anesthetized and unanaesthetised 4 male dogs aged 7 and 8 years old (» middle-aged male) (Table 1). The diameter of the penis, redness of skin, blood NOx concentration in the penis was used to assess the penile erection.…”
Section: No-loaded Npsmentioning
confidence: 99%
“…Chemical enhancement instead consists of adjusting the drug formulation by adding appropriate chemical substances that cause the swelling of skin barrier [104]. A further skin penetration enhancement strategy consists of the incorporation of the active substance into nanocarriers; such devices can be designed in order to possess physical and chemical properties that allow them to drive the drug across the skin barrier to reach the systemic circulation without affecting the outer skin integrity [105,106]. Moreover, it is possible to combine some pharmaceutical nanocarriers with textile material in order to produce wearable drug delivery devices.…”
Section: Skin Interaction With Drugs and Current Challenges In Dermentioning
confidence: 99%
“…In the work of Pereira [123] adapalene (logP = 8.5) loaded PCL nanocapsules were produced and topically applied: the high hydrophobicity of both carrier and drug facilitated diffusion in the SC but no further penetration was observed, making the system suitable for topical administration. Marto et al [70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103,104,105,106,107,108,109,110,111,112,113,114,115,116,117,118,119,120,121,122,123,124] incorporated an anti-inflammatory drug in starch-shelled nanoparticles by emulsion solvent evaporation method. The potential effectiveness of such topical formulation was evaluated both in vitro and in vivo on ra...…”
Section: Pharmaceutical Nanocarriers For Dermatological Applicationsmentioning
confidence: 99%